Managing your data risk: back to basics. (August 2015) - Richter, Chris
Abstract : It is estimated that enterprises spent more than 70bn on security technology in 2014, according to an industry analyst, and are expected to increase that spend by nearly 10% in 2015. 1 With such increased year-over-year expenditure, it would be easy to believe the enterprise sector is winning the battle against cyber-criminals. Wrong. Malware proliferation, network penetrations and data breaches continue to have an impact on organisations at an alarming rate and with increased consequences. A major challenge for organisations is that the cost to implement cyber-security defences will continue to rise as attacks become stealthier and more difficult to combat. Instead of spending more, businesses need to spend smarter. Rather than throwing money at the problem, it is more important to take a step back and conduct a carefully thought-out risk assessment. This way, companies can actually determine how best to secure their biggest asset – data – as Chris Richter of Level 3 Communications explains.